5(5y-2)+3(2y+6)=25(3y+2)-14y

Simple and best practice solution for 5(5y-2)+3(2y+6)=25(3y+2)-14y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(5y-2)+3(2y+6)=25(3y+2)-14y equation:



5(5y-2)+3(2y+6)=25(3y+2)-14y
We move all terms to the left:
5(5y-2)+3(2y+6)-(25(3y+2)-14y)=0
We multiply parentheses
25y+6y-(25(3y+2)-14y)-10+18=0
We calculate terms in parentheses: -(25(3y+2)-14y), so:
25(3y+2)-14y
We add all the numbers together, and all the variables
-14y+25(3y+2)
We multiply parentheses
-14y+75y+50
We add all the numbers together, and all the variables
61y+50
Back to the equation:
-(61y+50)
We add all the numbers together, and all the variables
31y-(61y+50)+8=0
We get rid of parentheses
31y-61y-50+8=0
We add all the numbers together, and all the variables
-30y-42=0
We move all terms containing y to the left, all other terms to the right
-30y=42
y=42/-30
y=-1+2/5

See similar equations:

| h/4− 2=2 | | x+1.3=2.25 | | 14x+14+13x+13=180 | | (k+4)(k-4)=9 | | -5(-4x+7)=3 | | 13x+13+14x+14=180 | | 16(x+3)=8(x-5)-5(x+4)-9 | | -7y+3(y-6)=-14 | | -12=-8z+18 | | -15+3x/7x=-43 | | -7y+3(y-6=-14 | | 25x=40+x | | 4=174-u | | -6x+2(x+6)=20 | | (4x+6)°+(11x-6)°=180 | | 2x^2(6x-8)+4=39 | | 286=-x+224 | | 4+2(z−7)=−3(3+z)+4z−2 | | -3=2/3(-1)+x | | 18x+3=15x+2 | | 8(w-4)-4w=-16 | | (5r+20)/15=(4r-24)/4 | | m-6/7=8 | | 12=4+4j | | -11x+10=13x-2 | | 15z^2+23z+4=0 | | n4−2=2 | | 7y-3(y-2)=6(y+1) | | 3/7=y/10 | | 5x+5=-1+x | | 4(3x-9)=-10 | | -1/2(2x-4)=-12 |

Equations solver categories